Семантичні типи контамінованих лексичних одиниць сучасної німецької мови - Рись, Лариса Федорівна; Пасик, Людмила Адамівна; Rys, Larysa F.; Pasyk, Lyudmyla Adamivna (Національний університет "Острозька академія", 2018)
У статті досліджується семантика лексичних одиниць, утворених шляхом контамінації – часткового накладання двох твірних основ одна на одну та одночасного їхнього утинання. Семантична інтерпретація контамінованих лексем базується на встановленні характеру взаємодії значень твірних основ та позначуваного поняття. Було виокремлено контаміновані лексеми із сурядним та підрядним співвідношеннями між складниками. У разі сурядного зв’язку розрізняємо ендоцентричні, екзоцентричні, синонімічні та антонімічні відношення між мотивуючими основами. У випадку підрядного зв’язку можливі означальні, обставинні (зокрема перший складник може вербалізувати місце, мету, засіб, причину найменованого явища), посесивні, асоціативні та ситуативні відношення між складниками контаміната. The article is devoted to the semantics of lexical units, formed as a result of blending in Modern German. Blending is understood as a word-building process of intentional creation of a new word by combining parts of two words after clipping and/or phonemic overlap of the constituents. The semantic interpretation of blended words deals with the detection and semantic classification of the relations between motivating morphemes, constituents of blends. The blended lexical units with coordinative and subordinate relations between constituents were distinguished. In case of the coordinative interpretation we differentiate between the following types: endocentric or additional reading (the blend denotes a pair consisting of both constituents); exocentric reading (the blend denotes a hybrid object possessing some features of both constituents), synonym reading (the both constituents have almost the same meaning) and antonym reading (constituents denote opposites). In case of the subordinate interpretation we distinguish between attributive, adverbial (the first constituent can verbalize a place, a mean, a purpose or a cause of the nominated phenomenon), possessive, associative and situational semantic relations between the constituents of the blended words. The observed semantic types of blends evidence that blending is developing according to the semantic patterns of compound words in the modern German language.
Semantic types of blended lexical units in modern German
Keywords: словотвір; контамінація; контамінована лексема; лексичне значення; word-building; blending; blended word; lexical meaning; relation between the constituents